PENGARUH MODEL PEMBELAJARAN PBL YANG DIDUKUNG MEDIA PAPAN GEOBOARD TERHADAP HASIL BELAJAR MATEMATIKA PESERTA DIDIK KELAS IV GUGUS SEMPU TAHUN PELAJARAN 2025/2026 - Kusuma Dewi, Liyandita; I Gusti Ngurah Triyana; Gusti Ayu Agung Riesa Mahendradhani (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This study aimed to determine the effect of the Problem Based Learning (PBL) model assisted by geoboard media on the mathematics learning outcomes of fourth-grade students in the Sempu Cluster for the 2025/2026 academic year. The background of this study was the low mathematics learning outcomes of students, especially on plane geometry material, caused by limited conceptual understanding and the lack of innovative learning media. This research used a quantitative approach with a quasi-experimental design employing the Posttest-Only Control Design. The experimental class was taught using the Problem Based Learning (PBL) model assisted by geoboard media, while the control class received conventional learning. Data were collected through learning outcome tests and analyzed using normality tests, homogeneity tests, N-Gain tests, and Independent Sample T-Tests. The results showed that the average learning outcomes of students in the experimental class were higher than those in the control class. Based on the results of the Independent Sample T-Test, the significance value was < 0.05, indicating that H₀ was rejected and Hₐ was accepted. This means that there was a significant effect of the Problem Based Learning (PBL) model assisted by geoboard media on the mathematics learning outcomes of fourth-grade students. Therefore, the PBL model assisted by geoboard media is effective in improving elementary school students’ mathematics learning outcomes.